Eco-epidemiological risk factors for Japanese encephalitis in the endemic region of North East India: a hospital-based case-control study - Bishnu Ram Das; Gitali Kakoti; Mandira Chetri; Pranabjit Biswanath (Encephalitis, 2022)
Purpose Japanese encephalitis (JE) has emerged as a major public health concern in North East India due to its complex eco-epidemiological risk factors. The objective of this study was to understand the various risk factors associated with JE infection in the endemic study location. Methods A hospital-based case-control study was conducted at Jorhat Medical College and Hospital from August 2017 to September 2018. The study participants included 49 confirmed JE cases with two control arms, one consisting of non-JE acute encephalitis syndrome (AES) patients (n = 91) and the other of non-JE non-AES patients (n = 140), admitted at the same time in the pediatric and medicine wards. A predesigned, pretested, structured questionnaire was used for data collection. Results Univariate analysis revealed the following to be risk factors: age at onset, sex, religion, immunization status, proximity to pigs, proximity to paddy fields (<100 m), use of a mosquito net, impregnated mosquito net, mosquito repellent, and outdoor activities. Multiple logistic regression analysis identified age at onset (adjusted odds ratio [AOR], 20.900; 95% confidence interval [CI], 2.210–31.815) and proximity to pigs (AOR, 4.190; 95% CI, 1.592–11.040) as risk factors for the first control arm and proximity to paddy fields (<100 m) (AOR, 8.470; 95% CI, 2.0251–35.438) was the only risk factor found for second control arm, whereas impregnated mosquito nets (AOR, 0.082; 95% CI, 0.009–0.725) and mosquito repellent (AOR, 0.173; 95% CI, 0.052–0.575) were found to be associated with the second control arm. Conclusion Age at onset, proximity to pigs, proximity to paddy fields (<100 m), impregnated mosquito nets, and mosquito repellent were the most significant risk factors for JE in the NE region to warrant public health actions.